Features of Atopic Reactivity in Schoolchildren with Severe Bronchial Asthma - U.I. Marusyk (Zaslavsky O.Yu., 2014)
The study involved 30 students with severe bronchial asthma and 30 children with moderate to severe course. Patients with severe bronchial asthma revealed a clear tendency to increase the relative content of interleukin 4 in peripheral blood, which indirectly indicates the severity of inflammation in the bronchi. Almost every second child suffering from severe bronchial asthma reported an increase in the concentration of immunoglobulin E (more than 545.3 IU/ml), and the odds ratio was 1.9 (95% CI 1.1-3.4). In the group of patients with severe bronchial asthma, cases of increased skin sensitivity to household allergens were significantly more frequent compared to the second group. Thus, the size of hyperemia over 15.0 mm was recorded in 81.5 % of children of the first group and only in 51.9 % of persons (Pϕ < 0.05) in the second one. Clinical and epidemiological risk and diagnostic value of individual indicators of atopic reactivity were determined to verify the phenotype of severe bronchial asthma.